2018
DOI: 10.3389/fneur.2018.00250
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Sex and Diabetes on Outcome After Ischemic Stroke

Abstract: BackgroundThe relationship between ischemic stroke (IS), diabetes mellitus (DM), and sex is intriguing. The aim of this study was to assess the effect modification of sex in the association between DM and short- and long-term disability and mortality in first-ever IS patients.MethodsIn a retrospective, observational, hospital-based study of a prospective series including first-ever IS patients from January 2006 until July 2011, differences in 3-month and 5-year mortality, and disability between diabetic and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
(43 reference statements)
1
13
1
1
Order By: Relevance
“…In some cohorts with acute stroke from any cause, diabetes was associated with mortality only in men 29–31. In our study, however, a modifying effect of sex was observed only for prediction of short-term mortality after ICH: pre-diabetes was prognostic in women only and diabetes in men only.…”
Section: Discussioncontrasting
confidence: 83%
“…In some cohorts with acute stroke from any cause, diabetes was associated with mortality only in men 29–31. In our study, however, a modifying effect of sex was observed only for prediction of short-term mortality after ICH: pre-diabetes was prognostic in women only and diabetes in men only.…”
Section: Discussioncontrasting
confidence: 83%
“…Furthermore, T2DM men had higher incidence rates of ischemic stroke than T2DM women. These trends are in accordance with what had been previously described in diabetic population [ 10 , 21 ]. Despite the American Heart Association/American Stroke Association having summarized the particularities of ischemic stroke in women, in part due to the increasing rates stroke mortality in women [ 22 ], virtually every study shows persistently higher ischemic stroke incidence rates in men.…”
Section: Discussionsupporting
confidence: 93%
“…Sex differences may be related to the incidence and outcomes of ischemic stroke among persons with diabetes [ 9 , 10 , 11 ]. Peters et al [ 9 ] concluded that diabetes had a greater impact in the risk of stroke among women than men (27% excess risk), independently of other stroke risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, women with diabetes had a higher risk of AKI than men. Previous studies have yielded equivocal results regarding the interaction between sex and diabetes mellitus in stroke outcomes, which could be due to ethnic differences between populations [21][22][23]. More research is needed to clearly establish the relationship between diabetes, sex and stroke outcomes in different populations.…”
Section: Discussionmentioning
confidence: 99%